PENGELOLAAN BELANJA DAMPAK JARING PENGAMAN SOSIAL DI MASA PANDEMI COVID-19 - Basri, Yesi Mutia; Prasetio, Yoland; Susilatri, Susilatri (Widya Mandala Surabaya Catholic University, 2022)
Research Purposes. This study aims to observe how the financial management of the Riau Province government in dealing with the impact of social safety nets.Research Method. A qualitative method with a sort of case study was used in the investigation. In-depth interviews, observation, and documentation are all used to acquire data. Triangulation techniques were utilized to assure data veracity.Research Result and Findings. The findings in the budgeting stage demonstrate refocused and reallocated of funds activities by Riau Provincial Government by allocating 100 million for persons affected by Covid-19 through BLT and basic food support. There was some un-valid data problem in the aid distribution to the community so that the assistance could not be fully disbursed to third parties. At the aid distribution stage, a problem was found, namely the amount of aid that was not fully received by the community due to an error in the aid distribution system. This study aids the government in formulating strategies for local financial management of social safety nets in the event of a disaster.